Extrusion-Based Printing of Myoblast-Loaded Fibrin Microthreads to Induce Myogenesis - Hanson S. Lee; Bryanna L. Samolyk; George D. Pins (Journal of Functional Biomaterials)
Large skeletal muscle injuries such as volumetric muscle loss (VML) disrupt native tissue structures, including biophysical and biochemical signaling cues that promote the regeneration of functional skeletal muscle. Various biofabrication strategies have been developed to create engineered skeletal muscle constructs that mimic native matrix and cellular microenvironments to enhance muscle regeneration; however, there remains a need to create scalable engineered tissues that provide mechanical stability as well as structural and spatiotemporal signaling cues to promote cell-mediated regeneration of contractile skeletal muscle. We describe a novel strategy for bioprinting multifunctional myoblast-loaded fibrin microthreads (myothreads) that recapitulate the cellular microniches to drive myogenesis and aligned myotube formation. We characterized myoblast alignment, myotube formation, and tensile properties of myothreads as a function of cell-loading density and culture time. We showed that increasing myoblast loading densities enhances myotube formation. Additionally, alignment analyses indicate that the bioprinting process confers myoblast alignment in the constructs. Finally, tensile characterizations suggest that myothreads possess the structural stability to serve as a potential platform for developing scalable muscle scaffolds. We anticipate that our myothread biofabrication approach will enable us to strategically investigate biophysical and biochemical signaling cues and cellular mechanisms that enhance functional skeletal muscle regeneration for the treatment of VML.